Biomarkers of folate and vitamin B12 and breast cancer risk: report from the EPIC cohort. Issue 6 (15th March 2017) - Matejcic, M.; de Batlle, J.; Ricci, C.; Biessy, C.; Perrier, F.; Huybrechts, I.; Weiderpass, E.; Boutron‐Ruault, M.C.; Cadeau, C.; His, M.; Cox, D.G.; Boeing, H.; et al.
Abstract : Epidemiological studies have reported inconsistent findings for the association between B vitamins and breast cancer (BC) risk. We investigated the relationship between biomarkers of folate and vitamin B12 and the risk of BC in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Plasma concentrations of folate and vitamin B12 were determined in 2, 491 BC cases individually matched to 2, 521 controls among women who provided baseline blood samples. Multivariable logistic regression models were used to estimate odds ratios by quartiles of either plasma B vitamin. Subgroup analyses by menopausal status, hormone receptor status of breast tumors (estrogen receptor [ER], progesterone receptor [PR] and human epidermal growth factor receptor 2 [HER2]), alcohol intake and MTHFR polymorphisms (677C > T and 1298A > C) were also performed. Plasma levels of folate and vitamin B12 were not significantly associated with the overall risk of BC or by hormone receptor status. A marginally positive association was found between vitamin B12 status and BC risk in women consuming above the median level of alcohol (ORQ4‐Q1  = 1.26; 95% CI 1.00–1.58; P trend  = 0.05). Vitamin B12 status was also positively associated with BC risk in women with plasma folate levels below the median value (ORQ4‐Q1  = 1.29; 95% CI 1.02–1.62; P trend  = 0.03). Overall, folate and vitamin B12 status was not clearly associated with BC risk in this prospective cohort study. However, potential interactions between vitamin B12 and alcohol or folate on the risk of BC deserve further investigation. Abstract : What's new? Does B‐vitamin intake play a role in breast cancer (BC) risk? Results have been inconsistent. In this analysis of data from a large, prospective European study, the authors found that, overall, folate and vitamin B12 status were not clearly associated with BC risk. However, the risk did seem to increase somewhat for women who had higher vitamin B12 levels and either low plasma folate or increased alcohol consumption. The authors suggest that this may involve nutrient‐nutrient or gene‐nutrient interactions, such as changes in DNA methylation, which require further investigation.